تعليل الأحاديث باختلاف الثقات عند المحدثين والأحناف وأثر ذلك على المجتمع الباكستاني (Al Basirah, 2020)
The purpose of the research is an empirical study of the impact of differenceof opinion of Hadith Scholars and Ahnaaf among the Jurists regardingdisagreement of the reliable reporters in narrating hadīth on PakistanCommunity. As Pakistan is the multi-jurisdictional community, hence numberof opinions on any topic may confuse Pakistani mind and it perceives as one isderived from Hadith and other is based on juristic opinion. This confusionprimarily prevailed due to negligence of difference of methodology amongMuhaddithin and Jurists regarding acceptance or rejection of Ahaad Hadith.Therefore, the main objective of the researh is to elaborate the methodologiesof both type of scholars but the study will be limited to the critical analysis ofthe difference of opinion on disagreement of the reliable reporters in narratinghadīth and its effect on Juristic Opinions derived from Sunnah. The researchwill primarily focus on view of Ahnaaf w.r.t Hadītth Scholars as hanafi fiqh isthe most prevailing madhhab among the famous school of thoughts inPakistan while Hadith Scholars are the main scholars of explaining HadithStudies.
Keywords: Disagreement (Ikhtilāf), Relaible Reporters, Narration, Muhaddithin, Al- Ahnaaf, Pakistani Community.